2005
DOI: 10.1016/j.exphem.2004.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Control of globin gene expression during development and erythroid differentiation

Abstract: Extensive studies during the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
314
2
22

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(347 citation statements)
references
References 86 publications
9
314
2
22
Order By: Relevance
“…[10][11][12][13] The cause of this variability is poorly understood. 11,12,29,30 HbF concentration in blood is determined by interactions among chromosome remodeling activities, transcription factors, genes modulating erythropoiesis, genetic elements linked to the b-globin gene cluster, the kinetics of erythroid cell differentiation and differential red cell survival (for reviews see Bank 31 and Stamatoyannopoulos 32 ). This complex regulatory environment provides ample opportunity for genetic modulation of HbF production.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] The cause of this variability is poorly understood. 11,12,29,30 HbF concentration in blood is determined by interactions among chromosome remodeling activities, transcription factors, genes modulating erythropoiesis, genetic elements linked to the b-globin gene cluster, the kinetics of erythroid cell differentiation and differential red cell survival (for reviews see Bank 31 and Stamatoyannopoulos 32 ). This complex regulatory environment provides ample opportunity for genetic modulation of HbF production.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrate that transgenic MCF7 cells induced to over-express HMGA1 proteins (i.e., "ON" cells) exhibit compromised nucleotide excision repair of UV-induced photoproducts both in a constitutively active HPRT gene allele (which exists in a more "open" or accessible chromatin structure; [8]) and the silent β-globin gene (which exists in a "closed", or compacted, chromatin structure; [11]) compared to non-HMGA1-expressing "OFF" cells. While repair of both gene loci was significantly inhibited in the presence of HMGA1 proteins, this effect was much more pronounced in the transcriptionally silent β-globin gene.…”
Section: Discussionmentioning
confidence: 88%
“…Utilizing a recently developed quantitative long-range PCR-based assay for measuring genespecific removal of UV-induced lesions [7], we assessed the efficiency of removal of UVinduced DNA damage in two different human genes: the hypoxanthine phosphoribosyl transferase (HPRT) gene, an allele of which is constitutively expressed in all normal somatic cells [8][9][10]), and the β-globin gene, which is transcriptionally silent in all cells but those of erythroid lineage [11]. These genes were chosen because microarray and other analyses indicated that HMGA1 proteins do not regulate the transcription of either gene in the cell lines being investigated (unpublished data), an important consideration given that these proteins can either positively or negatively regulate the transcription of a large number of genes in vivo (reviewed in: [12]).…”
Section: Introductionmentioning
confidence: 99%
“…However, nobody paid attention to this gene in the field of 'cancer'. Even physiologically, HBB expression is controlled intricately (Stamatoyannopoulos, 2005). In the viewpoint of cancer genetics, it strongly required further examination of the mechanism of the downregulation of HBB in anaplastic thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%